Block catiomer with flexible cationic segment enhances complexation with siRNA and the delivery performance in vitro. Issue 1 (31st December 2021) - Yang, Wenqian; Miyazaki, Takuya; Chen, Pengwen; Hong, Taehun; Naito, Mitsuru; Miyahara, Yuji; Matsumoto, Akira; Kataoka, Kazunori; Miyata, Kanjiro; Cabral, Horacio
ABSTRACT: RNA interference (RNAi) by small interfering RNAs (siRNAs) is a promising therapeutic approach. Because siRNA has limited intracellular access and is rapidly cleared in vivo, the success of RNAi depends on efficient delivery technologies. Particularly, polyion complexation between block catiomers and siRNA is a versatile approach for constructing effective carriers, such as unit polyion complexes (uPIC), core-shell polyion complex (PIC) micelles and vesicular siRNAsomes, by engineering the structure of block catiomers. In this regard, the flexibility of block catiomers could be an important parameter in the formation of PIC nanostructures with siRNA, though its effect remains unknown. Here, we studied the influence of block catiomer flexibility on the assembly of PIC structures with siRNA using a complementary polymeric system, i.e . poly(ethylene glycol)-poly(L-lysine) (PEG-PLL) and PEG-poly(glycidylbutylamine) (PEG-PGBA), which has a relatively more flexible polycation segment than PEG-PLL. Mixing PEG-PGBA with siRNA at molar ratios of primary amines in polymer to phosphates in the siRNA (N/P ratios) higher than 1.5 promoted the multimolecular association of uPICs, whereas PEG-PLL formed uPIC at all N/P ratios higher than 1. Moreover, uPICs from PEG-PGBA were more stable against counter polyanion exchange than uPICs from PEG-PLL, probably due to a favorable complexation process, as suggested by computational studies of siRNA/block catiomer binding. In in vitro experiments, PEG-PGBA uPICs promoted effective intracellular delivery of siRNA and efficient gene knockdown. Our results indicate the significance of polycation flexibility on assembling PIC structures with siRNA, and its potential for developing innovative delivery systems. Graphical abstract: uf0001